Learning difficulties in solving mathematical story problem length measurement based on newman’s error analysis - Manuputty, Yolanda Tirza Theresia; Setiani, Rahyu (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Fourth-grade students at SD Negeri Samir made mistakes in solving story problems because the students had difficulty learning mathematics. This research aims to describe learning difficulties in solving mathematics story problems on length measurement material based on Newman’s Error Analysis in the study of fourth-grade students at SD Negeri Samir. The type and approach of this research is a qualitative case study. The research location is Samir Elementary School, Tulungagung. The subjects of this research were six fourth-grade students at SD Negeri Samir. Data collection methods are observation, interviews, and documentation. The instruments used were an observation guide, an interview guide, and a document in the form of a long story question measuring four items. The results of this research are as follows: (1). Students have difficulty reading words (AS, RPP) and reading length measurement units (AS, MRA, RPP, RAIH, JSR, MZF); (2). Students experience verbal difficulties, namely determining story problem information based on numbers, punctuation marks, and words rather than understanding the story problem (AS, RPP); (3). Students experience verbal difficulties, namely being unable to determine and write the correct solution formula according to the request for the story problem (AS); (4). Students have difficulty applying the principles, namely difficulty converting length units (AS, MRA, RPP, RAIH, JSR, MZF); (5). Students have difficulty understanding the correct use of symbols (RAIH). The research results conclude that AS, MRA, RPP, RAIH, JSR, and MZF students experience difficulty learning language and reading, solving verbal problems, understanding symbols, and applying principles.